INVESTIGATION OF THE EFFECTIVENESS OF FIRE RISK EMERGENCY PREPAREDNESS IN HIGH INSTITUTIONS IN THE NIGER DELTA REGION OF NIGERIA - Ibekwe Nseabasi, Godwin; Ify Nwaogazie; Olufemi Adesope; John Ugbebor (International Journal of Innovations in Engineering Research and Technology, 2024)
The study was carried out to investigate the effectiveness of fire risk emergency preparedness in high institutions in the Niger delta region of Nigeria. Three objectives and two hypotheses were raised to captivate the aim the of the study. The study adopted survey design, and systematic and purposive sampling technique was used to select eight high institutions from eight states in the Niger-Delta while Krejcie and Morgan, table was used to determine sample size of three hundred and twenty-three (382) student, Structured questionnaire, designed using 5-point Likert scale, was used for data collection. Descriptive statistics (percentage and weighted mean score WMS) and ANOVA were used for data analysis. The results of descriptive statistic showed that; the current and existing fire risk assessment methods in the high institution in the Niger-delta is below average (46.80%), the level of awareness and knowledge of students and other stakeholders on fire risk assessment methods among the high institutions in the Niger delta is substantially good (WMS= 3.79 > 3.00) and the level of effectiveness of existing fire risk assessment methods. in the high institution in the study area is substantially good (WMS= 3.91 > 3.00). The ANOVA results used to test the hypotheses revealed that; there is no significant variation in awareness and knowledge levels regarding fire risk assessment methods across the eight states (p-value 0.883 > 0.05 significance level) and there is no significant variation in level of effectiveness of the fire risk assessment methods across the high institutions in the eight states (p-value 0.238 > 0.05 significance level). It was concluded that the effectiveness of fire risk emergency preparedness in high institutions in the Niger delta region of Nigeria is good but required more improvement. It was recommended that the authorities and fire service department in the high institution should improve coordination in emergency response by addressing identified areas for enhancement, such as equipment readiness and communication systems